Assessment of the Nutritional Status of the Children with Acute Leukemia on Chemotherapy in Karbala City - Dheyaa Aldeen Nawfal Al-khateeb; Ali Hussein Al-hafidh; Usama Ahmed Hadi Al-jumaily (Journal of Techniques)
Acute leukemia is the most cancer has frequency in children, Malnutrition is one of the common complications of children with cancer, and malnutrition has been identified as a significant factor in treatment tolerance, increased morbidity, poor prognosis, reduced quality of life, and higher healthcare expenses.